Cultural space of Russia - Bokov, Andrey (project baikal, 2024)
With the author’s permission, Project Baikal publishes excerpts from Andrey Bokov’s forthcoming book on Russian cultural space. The article provides a comparative analysis of Russian cultural space in comparison with European and Eastern cultural spaces; transformations started by Peter the Great and actively continued under Catherine the Great; subsequent stages, including the Soviet practice of spatial construction and the latest transformations.